The First Report of the Aphid Genus Macromyzus (Hemiptera: Aphididae) from Laos, with a Description of a New Species and Its Taxonomic Position - Minho Lee; Mariusz Kanturski; Chitpasong Santammavong; Seunghwan Lee (Insects)
In this paper, the aphid genus Macromyzus Takahashi, 1960 is reported for the first time from Laos. A detailed description of the apterous viviparous female of a new species, Macromyzus (Macromyzus) diplazius sp. nov. associated with Diplazium esculentum is provided. For the first time, we conduct scanning electron microscopy (SEM) to examine the morphology and sensilla (antennae, mouthparts, and legs) of the representative of this genus. Furthermore, we update the taxonomic definition of the subgenus Macromyzus based on morphological characteristics, discuss the taxonomic position of the new species, and provide an identification key to all known Macromyzus species.